THE STRATEGIC ROLE OF ENGLISH IN IMPLEMENTING INSTAGRAM MARKETING STRATEGIES: AN INTEGRATED SWOT PERSPECTIVE - Fahira; Riny Jefri; Fatimah Hidayahni Amin (International Journal of Business English and Communication, 2026)
This research is a qualitative descriptive study which aims to identify and describe strengths and weaknesses, opportunities and threats in understanding the role of English in implementing marketing strategies using Instagram. Data was obtained through documents on Instagram. The findings show that PT. Bumi Sarana Beton effectively uses English in their Instagram posts to showcase their products, showing professionalism and international appeal. However, the use of English on Instagram is limited, with non-standard usage including English words, regional languages, and abbreviations. Lack of English proficiency may hinder Kalla Beton's global growth, engagement from diverse users, and negatively impact brand reputation. English-language content can increase accessibility and engagement, potentially expanding reach to a wider audience. However, a lack of English proficiency in Instagram marketing could hinder Kalla Beton's global growth and negatively impact its reputation.